Aerobic exercise improves memory and prevents cognitive deficits of relevance to schizophrenia in an animal model. (July 2020) - Mitsadali, Idil; Grayson, Ben; Idris, Nagi F; Watson, Linzi; Burgess, Matthew; Neill, Joanna
Introduction and objectives: Cognitive impairment associated with schizophrenia (CIAS) greatly reduces patients' functionality, and remains an unmet clinical need. The sub-chronic phencyclidine (scPCP) rat model is commonly employed in studying CIAS. We have previously shown that voluntary exercise reverses impairments in novel object recognition (NOR) induced by scPCP. However, there has not been a longitudinal study investigating the potential protective effects of exercise in a model of CIAS. This study aimed to investigate the pro-cognitive and protective effects of exercise on CIAS using the translational NOR and attentional set-shifting tasks (ASST). Methods: Female Lister Hooded rats were either exercised (wheel running for one hour per day, five days per week, for six weeks; n =20) or not ( n =20) and then tested in a natural-forgetting NOR test. Rats in each group were then administered either PCP (2 mg/kg intraperitoneally (i.p.)) or saline solution (1 mL/kg i.p.) for seven days, followed by seven days washout. Three NOR tests were conducted immediately and two and nine weeks after washout, and a natural-forgetting NOR test was carried out again eight weeks post washout. Rats were trained and tested in ASST from week 6 to week 10 post washout. Results: Non-exercised rats displayed a deficit in both of the natural-forgetting NOR tests, whereas exercised rats did not. The scPCP exercise group did not show the expected deficit in NOR at any time point, and had a significantly ameliorated deficit in the ASST compared to the scPCP control group. Conclusion: Voluntary exercise has long-lasting pro-cognitive and protective effects in two cognitive domains. Exercise improves cognition and could provide protection against CIAS.